Mitochondrial respiration of human platelets in young adult and advanced age - Seahorse or O2k? - Jedlička, J; Kunc, R; Kuncová, J (Physiological research, 2021)
The objective of the present study was to evaluate platelet mitochondrial oxygen consumption using high-resolution respirometry (HRR) and metabolic flux analysis (MFA) and to verify the effect of advanced age on these parameters. HRR was used to analyze permeabilized and intact platelets, MFA to measure oxygen consumption rates (OCR), extracellular acidification rates (ECAR) and ATP production rate in intact fixed platelets. Two groups of healthy volunteers were included in the study: YOUNG (20-42 years, n=44) and older adults (OLD; 70-89 years; n=15). Compared to YOUNG donors, platelets from group OLD participants displayed significantly lower values of oxygen consumption in the Complex II-linked phosphorylating and uncoupled states and the Complex IV activity in HRR protocols for permeabilized cells and significantly lower resting and uncoupled respirations in intact cells when analyzed by both methods. In addition, mitochondrial ATP production rate was also significantly lower in platelets isolated from older adults. Variables measured by both methods from the same bloods correlated significantly, nevertheless those acquired by MFA were higher than those measured using HRR. In conclusion, the study verifies compromised mitochondrial respiration and oxidative ATP production in the platelets of aged persons and documents good compatibility of the two most widely used methods for determining the global performance of the electron-transporting system, i.e. HRR and MFA.
Keywords: Mitochondria; adenosintrifosfát; Humans; buněčné dýchání; Oxygen Consumption; analýza metabolického toku; Female; Aged; mladý dospělý; dospělí; trombocyty; stárnutí; věkové faktory; senioři; lidé; mitochondrie; Aging; Adult; Blood Platelets; Adenosine Triphosphate; Energy Metabolism; ženské pohlaví; energetický metabolismus; Male; Hydrogen-Ion Concentration; spotřeba kyslíku; Aged, 80 and over; Metabolic Flux Analysis; Young Adult; senioři nad 80 let; Age Factors; mužské pohlaví; koncentrace vodíkových iontů; Cell Respiration